Star wars and the history of transmedia storytelling - Guynes, Sean and Hassler-Forest, Dan (Transmedia, 2018)
This collection offers vital new conceptual and methodological tools for understanding the ways in which transmedia storytelling and the industrial logic of media franchising have developed in concert over the past four decades. In emphasizing that Star Wars is both a media franchise and a transmedia storyworld, the essays in this book emphasize the complex negotiations between culture and industry that have shaped not only the brand and its many narrative threads, but also the larger organization of the transnational media landscape.
https://katalog.adlr.link/Record/0-1042463328